Implementation of Project-Based Learning Models with a STEM Approach to Understanding Student Concepts in Spatial Geometry - Aslan Aslan; Jumalia Jumalia; Asdar Asdar (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2026)
Indonesian students' mathematical literacy skills remain low, especially in spatial geometry, which requires visualization and a deep understanding of concepts. Conventional learning methods that focus on procedures and memorizing formulas have not been able to facilitate optimal knowledge construction, giving rise to various misconceptions. This study aims to analyze the implementation of the Project-Based Learning (PjBL) model integrated with the STEM approach and its effect on students' conceptual understanding of spatial geometry. The research uses a qualitative approach with a literature review method of national and international journal articles published in the last ten years. The data were analyzed using content analysis to identify consistent patterns of findings related to PjBL-STEM in geometry learning. The synthesis results show that PjBL-STEM significantly improves students' conceptual understanding, mathematical creative thinking skills, and spatial visualization. Contextual project-based learning shifts the learning orientation from memorization to conceptual understanding through activities of designing, constructing, and analyzing real objects. PjBL-STEM is a relevant approach to improve conceptual understanding and develop 21st-century skills. Its success requires careful planning, adequate teacher competence, and facility support for sustainable implementation.